Amarna gypsite: A new source of gypsum for ancient Egypt. (February 2017) - Harrell, James A.
Abstract: Gypsum was widely employed in Egypt for plaster and mortar from late Predynastic times onward with the most extensive and varied use of this mineral occurring at Amarna (ancient Akhetaten ) during the New Kingdom's Eighteenth Dynasty. It is traditionally thought the gypsum was obtained from the Faiyum Depression, but a new and larger source has been discovered on top of the limestone plateau to the north and east of Amarna. Here there are nearly three square kilometres of quarries dating mainly from the Old to New Kingdoms. The gypsum occurs in a thin soil on the limestone, forming a calcite-rich deposit known as gypsite. The total calcium sulfate content of gypsite samples (gypsum + bassanite + anhydrite) ranges from 24 to 74% with calcite comprising nearly all the remainder. Graphic abstract: Highlights: The discovery of the first known ancient gypsite quarries in Egypt. The determination of the anhydrite, bassanite and gypsum contents of gypsite soil. The suggestion, with supporting evidence, that gypsite was a major, if not the principal, source of gypsum for ancient Egypt.